2021
DOI: 10.2147/sar.s291869
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Use Among Reproductive Age Women in Ethiopia: Evidence from the National Health Survey

Abstract: Purpose To assess the prevalence and determinants of current tobacco use among reproductive-age women in Ethiopia. Methods A cross-sectional study was conducted by utilizing secondary data taken from the Ethiopian Demographic Health Survey of 2016. Descriptive statistics and logistic regressions were used to analyze the data. The odds ratio with a 95% confidence interval was considered to interpret associations and a significant association was stated at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 30 publications
5
7
0
Order By: Relevance
“…We found that while age 25-34 increased the odds of female cigarette smoking, age 15-24 reduced their likelihood of smoking daily. The findings of the current study are consistent with the evidence from previous studies [ 5 , 18 , 19 , 27 ], but differ from one study in which younger ages were predisposed to smoking [ 26 ]. As explained in a prior study, low prevalence among young women might be related to the effect of the ban on advertising and the increase in tobacco taxes [ 18 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We found that while age 25-34 increased the odds of female cigarette smoking, age 15-24 reduced their likelihood of smoking daily. The findings of the current study are consistent with the evidence from previous studies [ 5 , 18 , 19 , 27 ], but differ from one study in which younger ages were predisposed to smoking [ 26 ]. As explained in a prior study, low prevalence among young women might be related to the effect of the ban on advertising and the increase in tobacco taxes [ 18 ].…”
Section: Discussionsupporting
confidence: 89%
“…This study’s finding that being formerly married (divorced/separated/widowed) increased the likelihood of smoking and smoking every day among women is supported by evidence of higher odds of smoking among formerly married women from Ethiopia, Kenya and Iran [ 18 , 27 , 47 ]. In contrast, a prior study found that being married constituted a risk factor for smoking among women in Iran [ 5 ], where intrafamily conflicts, show-off and independence, and gender-equality symbols are associated with cigarette smoking among women [ 46 ].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Second, we aggregated the scores of individuals at the community-level to derive the proportion of participants with high exposure for every community/cluster. Most individual and communitylevel explanatory variables were chosen based on similar factors considered in previous literatures on tobacco use as well as their availability in the data files [24,[43][44][45][46][47].…”
Section: Independent Variablesmentioning
confidence: 99%